Electrospun carbon nanofibers loaded with spinel-type cobalt oxide as bifunctional catalysts for enhanced oxygen electrocatalysis. (June 2019) - Alegre, C.; Busacca, C.; Di Blasi, A.; Di Blasi, O.; Aricò, A.S.; Antonucci, V.; Modica, E.; Baglio, V.
Highlights: Bifunctional oxygen electrodes based on a Co3 O4 spinel-type oxide were evaluated. Carbon nanofibers loaded with Co3 O4 were synthesized by electrospinning. Co3 O4 /CNF showed a low overpotential for the OER and a remarkable reversibility. Co3 O4 /CNF is a promising material to be employed in air electrodes of metal-air batteries. Abstract: The electrocatalysis of oxygen in alkaline media is a challenging issue, influencing the performance of many electrochemical devices: fuel cells, unitized regenerative fuel cells, electrolyzers and metal-air batteries. This new manuscript proposes the synthesis of graphitic carbon nanofibers obtained by electrospinning with a cobalt-based spinel oxide, Co3 O4 /CNF. By means of a simple, reproducible and scalable method, a bifunctional catalyst with a promising performance is obtained, being able of carrying out the electrocatalysis of oxygen (oxidation of water, evolution and reduction of oxygen) in a basic solution. The combination of the active species on cobalt oxide (Co 2+, Co 3+ and Co-Nx ), along with active species in the carbon nanofiber (graphitic and pyridinic N), gives rise to a catalyst with a remarkable reversibility (difference between E10 mA/cm2 (evolution) and Ehalf-wave-potential (reduction)): ΔE =795 mV), a low over-potential for the evolution of oxygen (η =416 mV) and 919 mV of oxygen reduction onset potential, very similar to that of a benchmark catalyst, Pt/C.